A novel testing and theoretical approach for air-source heat-pump water heater with flash tank vapor-injection. (1st December 2022) - Xianglong, Liu; Guang, Hu; Zhi, Zeng; Ping, Wang; Liping, Zeng; Xiaohua, Li
Abstract: Air-source heat-pump (ASHP) water heater provides an important low-carbon solution for domestic water heating, which regains interest in the context of pursuing global carbon neutrality. In this study, a novel testing and theoretical approach is proposed for ASHP water heater with flash tank vapor-injection by retrofitting the testing methods of state points. Five flash tank vapor-injections with different temperature levels are tested and verified the testing method for ASHP water heater. On basis of the tested compressor suction temperature, exhaust temperature, electronic expansion valve pre-throttle temperature, electronic expansion valve throttling temperature and vapor-injection temperature, a thermodynamic analysis is conducted to determine the system performances. The relationship between the vapor-injection pressure ratio, system heating capacity and COP is identified by adjusting the expansion valve opening degree of the system. The results show that the COP of the system firstly decreases and subsequently increases with the increase in vapor-injection pressure ratio, and the minimum COP appears when the vapor-injection pressure ratio is 0.3. This study provides new insights into the advanced ASHP water heater.